How Winery Tourism Experience Builds Brand Image and Brand Loyalty - Annamma Joy; Seyee Yoon; Bianca Grohmann; Kathryn LaTour (Wine Business Journal)
This research examines the role of the winery tourism experience in the formation of brand image and brand loyalty. A qualitative analysis of 2540 TripAdvisor reviews—a user-generated form of electronic word of mouth—of four wineries of the Okanagan Valley posted over six years (2014-2020) reveals not only Pine and Gilmore’s (1999) four categories of consumer experiences (i.e., esthetics, education, entertainment, and escape), but also an additional factor (i.e., social interactions with employees and other visitors). The TripAdvisor reviews also show that—based on their winery tourism experiences—consumers express differentiated brand image impressions associated with wineries and brand loyalty. The contribution of this research lies in the identification of social interactions as a complementary dimension of winery tourism experiences, and in linking winery tourism experiences with brand image and brand loyalty. From a theoretical perspective, the findings encourage a greater integration of the consumer experience and the brand image and loyalty literature, as well as quantitative research examining their relation. The findings also have managerial implications for brand experience management in the wine tourism sector.